Accuracy of cut-off value by measurement of third molar index: Study of a Colombian sample. (April 2016) - De Luca, Stefano; Aguilar, Lina; Rivera, Marcela; Palacio, Luz Andrea Velandia; Riccomi, Giulia; Bestetti, Fiorella; Cameriere, Roberto
Highlights: 318 digital orthopantomographs from Colombia were analysed. The accuracy of the cut-off value of 0.08 was analysed. Repeatability and reproducibility are high for intra- and inter-observer error. The proportion of correctly classified individuals was high for girls and boys. The sensitivity and specificity values were quite high. Abstract: The aim of this cross-sectional study was to test the accuracy of cut-off value of 0.08 by measurement of third molar index (I3M ) in assessing legal adult age of 18 years in a sample of Colombian children and young adults. Digital orthopantomographs of 288 Colombian children and young adults (163 girls and 125 boys), aged between 13 and 22 years, were analysed. Concordance correlation coefficient ( ρ c ) and κ statistics (Cohen's Kappa coefficient) showed that repeatability and reproducibility are high for both intra- and inter-observer error. κ statistics for intra- and inter-observer agreement in decision on adult or minor was 0.913 and 0.877, respectively. Age distribution gradually decreases as I 3M increases in both girls and boys. For girls, the sensitivity test was 95.1% (95% CI 87.1%–95%) and specificity was 93.8% (95% CI 87.1%–98.8%). The proportion of correctly classified individuals was 95.1%. For boys, the sensitivity test was 91.7% (95% CI 85.1%–96.8%) and specificity was 90.6% (95% CI 82.1%–97.8%). The proportion of correctly classified individuals was 89.7%. The cut-off value of 0.08 is highly useful to determine if a subject is 18 years of age or older or not.